Guidelines for the Standardization of Rehabilitation Medicine Association Standards（2025 Edition） - CHEN Hanbo; YAN Tiebin; SHI Xiu'e; WU Ming; CHEN Wenhua; WANG Yulong; WU Wei; DUAN Zhouying; LEI Lei; BI Sheng; LU Xiao; SONG Zhenhua; et al. (康复学报, 2025)
As an integral component of China's standardization system, rehabilitation medicine group standards play a pivotal role in regulating clinical practice, ensuring care quality, and nurturing rehabilitation professionals. Grounded in the Standardization Law of the People's Republic of China and drawing on the practical experience of the Chinese Association of Rehabilitation Medicine, the Guidelines for the Standardization of Rehabilitation Medicine Group Standards aim to establish a systematic framework for the development of these standards and foster the field's regulated development. The Guidelines detail the principles for the formulation of rehabilitation medicine group standards, their scope, the qualifications of the entities involved, and the technical specifications. They highlight the importance of combining evidence-based practices with clinical experience in the development of these standards, articulate the foundational principles of openness, transparency, and consensus, and outline the comprehensive workflow from proposal to final publication and periodic review, providing concrete recommendations for the dissemination of the standards. By enhancing the quality of rehabilitation medicine group standards, the Guidelines will promote the standardization of rehabilitation medical services and advance the development of rehabilitation medicine in China.